Dermatofibrosarcoma protuberans in children and adolescents: The European Paediatric Soft Tissue Sarcoma Study Group prospective trial (EpSSG NRSTS 2005). Issue 10 (18th June 2020) - Brennan, Bernadette; Zanetti, Ilaria; De Salvo, Gian Luca; Orbach, Daniel; Gallego, Soledad; Francotte, Nadine; Schifflers, Stefan; Van Noesel, Max; Kelsey, Anna; Casanova, Michela; Dagrada, Gian Paolo; Collini, Paola; et al.
Abstract: Background: As dermatofibrosarcoma protuberans (DFSP) are rare with no prospective series within paediatric sarcoma trials, the European Paediatric Soft Tissue Sarcoma Study Group (EpSSG) examined the clinical data and outcomes of DFSP enrolled in a multinational study of non‐rhabdomyosarcoma soft tissue sarcomas (NRSTS). Patients and methods: Forty‐six patients with confirmed DFSP were enrolled into the EpSSG NRSTS 2005 study. All had surgical resection and none had any further therapy at diagnosis. Results: The median age at diagnosis was 6.9 years (range 0.4‐17.5). All patients had localised disease, and the majority had small <5 cm tumours (93%), and 76% had Intergroup Rhabdomyosarcoma Study (IRS) I tumours. All patients had up front surgery, 32 requiring two operations. There were 11 patients with IRS II tumours, of which only two went on to have a local recurrence. After a median follow up of 49.0 months (range 4.2‐130.9), all patients were alive at the time of this report, with 5‐year event‐free survival of 92.6% (CI 78.8‐97.6) with a 100% overall survival. Conclusion: This report demonstrates the ability to run prospective paediatric studies in NRSTS in multiple European countries, with reasonable numbers of DFSP patients, with few events and no deaths, and hence excellent outcomes.